Public Service Based on Local Wisdom - Zainal Abidin Rengifurwarin; Mike Jurnida Rolobessy (Program Pascasarjana Universitas Negeri Makassar, 2021)
Local wisdom is a determinant in providing the best service to the community. The research approach uses descriptive qualitative. The location of the research was carried out in the South Sulawesi Provincial Government. Data collection techniques used observation, interviews and documentation with an analytical approach, namely: 1) Data Collection, 2) Data Presentation, 3) Data Condensation, 4) Conclusion drawing/verification. The results of the study indicate that public services have been running well, this is tied to the existence of a brotherly bond between service providers and service recipients with the slogan Siri' Na Pacce. However, the government still faces obstacles, especially people who have different characteristics and needs.